A Little Experience Goes a Long Way: Chlormethine/Mechlorethamine Treatment Duration as a Function of Clinician-Level Patient Volume for Mycosis Fungoides Cutaneous T-Cell Lymphoma (MF-CTCL)—A Retrospective Cohort Study - Querfeld, Christiane; Pacheco, Theresa; Haverkos, Bradley; Binder, Gary; Angello, James; Poligone, Brian (Frontiers in Medicine, 2021)
Topical chlormethine yields high response rates in mycosis fungoides cutaneous T-cell lymphoma with early discontinuation often attributed to skin reactions. We evaluated over 4000 patients and found an association of clinician case volume with treatment duration and early discontinuation of chlormethine gel. The minority of clinicians with high patient volume markedly outperformed clinicians with only few patients on both outcome parameters, yet case volume as low as 5 patients seemed to mark a threshold for avoiding early discontinuation of treatment regimen.